Landscape spatial configuration is a key driver of wild bee demographics. (20th November 2016) - Neokosmidis, Lazaros; Tscheulin, Thomas; Devalez, Jelle; Petanidou, Theodora
Abstract: The majority of studies investigating the effects of landscape composition and configuration on bee populations have been conducted in regions of intensive agricultural production, ignoring regions which are dominated by seminatural habitats, such as the islands of the Aegean Archipelago. In addition, research so far has focused on the landscape impacts on bees sampled in cropped fields while the landscape effects on bees inhabiting seminatural habitats are understudied. Here, we investigate the impact of the landscape on wild bee assemblages in 66 phryganic (low scrubland) communities on 8 Aegean islands. We computed landscape metrics (total area and total perimeter–area ratio) in 4 concentric circles (250, 500, 750, and 1000 m) around the center of each bee sampling site including 3 habitat groups (namely phrygana, cultivated land, and natural forests). We further measured the local flower cover in 25 quadrats distributed randomly at the center of each sampling site. We found that the landscape scale is more important than the local scale in shaping abundance and species richness of bees. Furthermore, habitat configuration was more important than the total area of habitats, probably because it affects bees' movement across the landscape. Phrygana and natural forests had a positive effect on bee demographics, while cultivated land had a negative effect. This demonstrates that phryganic specialists drive bee assemblages in these seminatural landscapes. This finding, together with the shown importance of landscape scale, should be considered for the management of wild bees with special emphasis placed on the spatial configuration of seminatural habitats.